An Interactive Voice Response System for Postoperative Care in Primary Total Joint Arthroplasty Patients: A Pilot Study - Ayala-Ortiz, José L.; McCrosson, Matthew; Jacob, Roshan; Nagabooshanam, Vinoth A.; Mehta, Tapan; Al-Hardan, Waleed; McGwin, Gerald; Naranje, Sameer (Applied Clinical Informatics, 2025)
Effective postoperative care is crucial for the success of total joint arthroplasty (TJA) and prevention of unnecessary emergency department (ED) visits. We explore the feasibility and acceptability of utilizing an Interactive Voice Response System (IVRS) to enhance postoperative monitoring in primary TJA patients.This pilot study was conducted with 24 participants undergoing primary TJA randomly assigned to an intervention group receiving IVRS calls (n = 12) or a control group (n = 12) receiving standard postoperative follow-up. Feasibility and acceptability were assessed through patient satisfaction and willingness to participate. Outcome measures included the Short Form 36 Health Survey Questionnaire, the Hip Disability and Osteoarthritis Outcome Score (HOOS), the Knee Injury and Osteoarthritis Outcome Score (KOOS), and pain assessments using the Visual Analog Scale.The IVRS group exhibited a 92.3% retention rate, with 100% completion of the 12-week study. IVRS calls triggered 10 notifications, addressing pain control and respiratory concerns, leading to timely interventions and preventing ED visits. The IVRS demonstrated an 81% (95% confidence interval, 77.1–86.0%) overall response rate, with high patient satisfaction (92% finding calls “very useful”).This pilot study demonstrates the feasibility and acceptability of an IVRS-based postoperative follow-up system for TJA patients. Patients reported high satisfaction and expressed willingness to use the IVRS service again.
Keywords: telemedicine and telehealth; interactive response voice system; postoperative; arthroplasty; follow-up; patient satisfaction